The Use of Google Translate and U-Dictionary as Machine Translation for Translating Text: EFL College Student’s Preference and Perceptions - Ainan Ningrum; Dewi, Utami (ETERNAL (English Teaching Journal), 2024)
Several studies have investigated the effects of using Google Translate and U-Dictionary on translation products for English as a foreign language (EFL) student. However, students' preferences regarding these two machines’ translation for translating texts in EFL translation classes in Indonesia still seem relatively few and have not been much explored. This research aimed to determine which machine translation EFL college students prefer for translating their text. This study used a qualitative case study approach. In investigating students’ preferences, questionnaires, and in-depth interview were used as data collection tools. Seventeen students were selected by purposive sampling and were administered an online questionnaire. Then, students participated in in-depth interviews and obtained further information from an online questionnaire. We then analyzed the data using two techniques, including frequency counts for quantitative data and qualitative analysis through thematic analysis for qualitative data. The findings reveal that students prefer Google Translate over U-Dictionary for three reasons. First, they consider Google Translate as a complete machine translation with various features that help them translate text. Second, Google Translate increases student's knowledge of new vocabulary. Third, Google Translate makes the translation process more accessible for students. It is so easy to access. However, U-Dictionary also received high marks because students felt more confident in the accuracy of the U-Dictionary translation results. Therefore, it is believed that combining these two machines’ translations will make the student's translation process more accessible